EFFECTS OF MANAGING THE EXTENDED MARKETING MIX ON ORGANIZATION PERFORMANCE OF PARASTATALS IN NAIROBI - Wanyi, Mwangi Faith; Nyagindi, Joshua (European Journal of Business and Strategic Management, 2016)
Purpose: The study was an assessment of the effects of managing the extended marketing mix on organization performance of parastatals in Nairobi county. Methodology: The study used a descriptive sectional research design. The target population was 67 parastatals in Nairobi. A sample size of 2 parastatals was taken. The data collection instrument was a questionnaire. The data was analysed using descriptive statistics such as means and frequencies. The data analysis tool was statistical package for social sciences ( SPSS) version 17. The data was presented using bars and charts. Results: Findings indicated that customer service personnel in parastatals are unreliable since it does not do things correctly the first time. This is evidenced by the majority of respondents who indicated they strongly disagree and disagreed. Results also indicated that parastatals do not have effective means to manage people as this was evidenced by the majority of respondents who disagreed and strongly disagreed with the statements. These results indicate that people management in parastatals had not improved profitability of parastatals. Results further indicated that parastatals had poor management of physical evidence on market share, this is evidenced by majority of the respondents disagreed and strongly disagreed with the statements that the reception of my organization is spacious, well aerated and comfortable, the offices of my organizations have lifts and escalators, the physical allocation of my organization is easily accessible, the physical allocation of my organization had adequate security. Unique contribution to theory, practice and policy: This led to the conclusion that management of physical evidence had not improved the market share of parastatals. The study findings also indicated that majority of the respondents disagreed and strongly disagreed with the statements that their organization has clear processes for handling customer complaints, their organization has clearly laid out processes for identifying customer needs and requirements, their organization has clearly laid out processes for handling customer orders. This implies that parastatals have poor process management on business development. This led to the conclusion that process management had not improved the business development of parastatals